2016
DOI: 10.1016/j.endm.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

1-perfectly orientable K 4 -minor-free and outerplanar graphs

Abstract: A graph G is said to be 1-perfectly orientable if it has an orientation such that for every vertex v ∈ V (G), the out-neighborhood of v in D is a clique in G. In 1982, Skrien posed the problem of characterizing the class of 1-perfectly orientable graphs. This graph class forms a common generalization of the classes of chordal and circular arc graphs; however, while polynomially recognizable via a reduction to 2-SAT, no structural characterization of this intriguing class of graphs is known. Based on a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…One of the results from the table, namely the (tw, ω)-boundedness of the class of K 2,3 -induced-minor-free graphs, implies that the class of 1-perfectly orientable graphs is (tw, ω)-bounded. This answers a question raised by Brešar et al [10].…”
Section: Our Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…One of the results from the table, namely the (tw, ω)-boundedness of the class of K 2,3 -induced-minor-free graphs, implies that the class of 1-perfectly orientable graphs is (tw, ω)-bounded. This answers a question raised by Brešar et al [10].…”
Section: Our Resultssupporting
confidence: 67%
“…As explained by Belmonte et al [3] (and observed also in [10]), the following fact can be derived from the proof of Theorem 9 in [38].…”
Section: Back To Treewidthmentioning
confidence: 79%
See 1 more Smart Citation
“…A graph G is said to be 1-perfectly orientable if its edges can be oriented so that no vertex has a pair of non-adjacent out-neighbors. The class of 1-perfectly orientable graphs was introduced in 1982 by Skrien [108] and studied by Bang-Jensen et al [6] and more recently by Hartinger and Milanič [80] and Brešar et al [28]. While the class of 1-perfectly orientable graphs is known to be a common generalization of the classes of chordal graphs and circular-arc graphs, the structure of graphs in this class remains elusive.…”
Section: Reducing the Problem To Triconnected Componentsmentioning
confidence: 99%
“…Studying the structure of B 1 -free orientable graphs has caught the interest of several authors. In particular, Hartinger and Milanic, and the same authors with Brešar and Kos, have thoroughly studied this family in a series of papers [5,7,8]. We will follow their terminology and call the class of {B 1 }-graphs, 1-perfectly-orientable graphs (1-p.o.…”
Section: Introductionmentioning
confidence: 99%